Validating Molecular Markers for Barley Leaf Rust Resistance Genes Rph20 and Rph24 - Dracatos, P M (Plant disease, 2021)
Improving resistance to barley leaf rust (caused by Puccinia hordei) is an important breeding objective in most barley growing regions worldwide. The development and subsequent utilization of high-throughput PCR-based codominant molecular markers remains an effective approach to select genotypes with multiple effective resistance genes, permitting efficient gene deployment and stewardship. The genes Rph20 and Rph24 confer widely effective adult plant resistance (APR) to leaf rust, are common in European and Australian barley germplasm (often in combination), and act interactively to confer high levels of resistance. Here we report on the development and validation of codominant insertion-deletion (indel) based PCR markers that are highly predictive for the resistance alleles Rph20.ai and Rph24.an (both referred to as Rph20 and Rph24)